先化简再求值 xyz-【-x的平方y+(xyz-x的平方z)】-x的平方z,其中x=-1,y=-2,z=三分之一
3个回答
原式=xyz-(-x的平方y+xyz-x的平方z)-x的平方z
=xyz+x的平方y-xyz+x的平方z-x的平方z
=x的平方y
=1×(-2)
=-2
相关问题
化简求值x的平方y-【-x的平方y+(xyz-x的平方z)+xyz】-x的平方z,当x=-1,y=
先化简,再求值:3xyz+2(x²y+y²z-xyz)-xyz+2z²x,其中x=1、y=-1、z=2;
化简求值:3x的平方y-[2x的平方y-(2xyz-x的平方-x的平方z)]+4(x的平方z-xyz).其中
先化简,后求值.已知x=-2,y=-3,z=1,求3x的平方-[2x的平方y-(2xyz-x的平方z)-4x的平方z]-
3x的平方y-[2x的平方y-(2xyz-x的平方z)-4x的平方z]-xyz,其中x=-2,y=-3,z=1
求值:3x的平方y-(2x的平方y-(2xyz-x的平方z)-4x的平方z),其中x=-2,y=-3,z=1
(3x^2z+2yz^2-xyz)+2xyz-3yz^2+x^2z,其中x=2,y=-1,z=1求先化简,再求值
x平方+y平方+2z平方-2x+4y+4z+7=0,求xyz的值
如果xyz=1,x+y+z=2,x的平方+y的平方+z的平方=3,求(1/xy+z-1)+(1/yz+x+1)+(1/z
xyz=1 x+y+z=2 x平方+y平方+z平方=16 求(xy+2z)分之1+(yz+2x)分之1+(zx+2y)分